Auction-based allocation of shared electricity storage resources through physical storage rights - Tom Brijs; Daniel Huppmann; Sauleh Siddiqui; Ronnie Belmans (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This article proposes a new electricity storage business model based on multiple simultaneously considered revenue streams, which can be attributed to different market activities and players. These players thus share electricity storage resources and compete to obtain the right to use them in a dynamic allocation mechanism. It is based on the design of anew periodically organized auction to allocate shared storage resources through physical storage rights between different market players and ac-companying applications. Through such a flexibility platform owners of flexible resources can commercialize their flexible capacity over different applications, while market players looking for additional flexibility can obtain this through a pay-per-use principle and thus not having to make long-term investment commitments. As such, they can quickly adapt their portfolio according to the market situation. Alternatively, through such an allocation mechanism players can effectively share storage re-sources. Players may be incentivized to participate as they can share the investment cost, mitigate risk, exploit economies of scale, overcome regulatory barriers, and merge time-varying and player-dependent flexibility needs. The mechanism allocates the limited storage resources to the most valuable application for each market-clearing, based on the competing players' willingness-to-pay. An illustrative case study is provided in which three players share storage resources that are allocated through a daily auction with hourly market-clearings.
Keywords: D44; D47; L94; Q41; 330; electricity storage; shared storage resources; auction-based allocation; (Generalized) Nash Equilibrium; Mixed Complementarity Problem